Abrasive water-jet: controlled depth milling of titanium alloys - Fowler, Gary (2003)
Abrasive waterjet (AWJ) technology is used in a routine manner in manufacturing industry to cut materials that are difficult to cut by other methods. Whilst the technology for through cutting of materials is mature, the process is also being developed for controlled depth milling (CDM) of materials.